Voclosporin: First Approval: Voclosporin: First Approval - Heo, Young-A (Drugs (New York, N.Y.), 2021)
Voclosporin (Lupkynis ™ ) is an oral calcineurin inhibitor immunosuppressant that is being developed by Aurinia Pharmaceuticals. In January 2021, based on positive results from the pivotal phases II and III trials, oral voclosporin received its first approval in the USA for use in combination with a background immunosuppressive therapy regimen for adults with active lupus nephritis. Voclosporin is also being explored for the novel coronavirus disease 2019 (COVID-19) in kidney transplant recipients. This article summarizes the milestones in the development of voclosporin leading to this first approval for lupus nephritis.